Current molecular diagnostic approaches to systemic infections with Aspergillus species in patients with Hematological Malignancies - Buchheidt, Dieter; Hummel, Margit; Schleiermacher, Dietlind; Spiess, Birgit; Hehlmann, Rüdiger (Leukemia and lymphoma, 2004)
Within the recent years, novel molecular methods, especially PCR assays, have been developed to improve the diagnosis of invasive aspergillosis in patients with malignant hematological diseases being at high risk for this life-threatening infection. Early diagnosis and treatment are essential for adequate therapeutical management, which however, often remains difficult since most of the diagnostic tools used clinically at present either lack specificity or acceptable sensitivity. The clinical value, advantages and remaining problems of recently developed molecular approaches to detect the emerging fungal pathogen are reviewed.
Elektronische Reproduktion der Druckausgabe
Gesehen am 13.05.2022